Contextualising Historical and Cultural Identities with Exhibitions of the New National Museum in the Democratic Republic of Congo - Kwang-Su Kim (Modern Africa, 2020)
A new National Museum of the Democratic Republic of the Congo (MNRDC) was established as a cultural Official Development Assistant (ODA) project by the Korean government. It opened on 23 November 2019 in Kinshasa. The objectives of the new museum are to promote the history and culture of various ethnic groups, protect heritage and exhibit cultural diversity in order to unify the people and the nation, and educate the public about the DRC history and culture. However, the exhibitions do not meet the objectives of the National Museum nor do they contextualise the history and cultural identity of the DRC. In order for the MNRDC to function as a national museum or a central national museum, its exhibition must be reconstructed in such a way that meets its purposes while historical artefacts accurately representing the DRC’s history must be displayed.